(untitled) (Journal of Engineering, 2013)
The behavior of externally prestressed composite beams under short term loading has been studied. A computer program developed originally by Oukaili to evaluate curvature is modified to evaluate the deflection of prestressed composite beam under flexural load. The analysis model based on the deformation compatibility of entire structure that allows to determine the full history of strain and stress distribution along cross section depth, deflection and stress increment in the external tendons . The evaluation of curvatures for the composite beam involves iterations for computing the strains vectors at each node at any loading stage. The stress increment determined using equations depended on the member deflection at points of connection. The stress increment determined using equations depended on the member deflection at points of connection. The proposed model results for load –deflection response are compared with experimental data taken from Auyyb’s beams. For beams with straight tendon profile the average discrepancy reached 5.77%, 8.48% and 5.23% corresponding to the 0.25, 0.5 and 0.75 of the maximum load, respectively. For beams with the draped tendon profile, the average discrepancy of the analytical deflections values reached 15.5%, 5.8% and 6.45% corresponding to the 0.25, 0.5 and 0.75 of maximum load, respectively.